Coparenting Questionnaire (CQ): Adaptation and Validity Evidences for Brazilian Context - Padilha, Amanda Porto; Varas, Giuliana Violeta Vásquez; Bosa, Juliane Callegaro (Paidéia (Ribeirão Preto), 2023)
Co-parenting is the reciprocal effort between two caregivers to raise a child and is important in the mental health of families. This study aims to describe the adaptation procedures and initial evidence of validity of the Co-parenting Questionnaire (CQ) for Brazil. The adaptation was carried out according to the stages: translation; synthesis of translated versions; evaluation by experts and target audience; and reverse translation. To assess its factorial structure, confirmatory factor analyzes were performed in multifactorial and bi-factorial models in a sample of 590 mothers/fathers aged 21 to 60 years (M = 36.24; SD = 5.88) residing in 21 states of Brazil. The CQ presented adequate adjustments for a correlated multifactorial solution and for the bifactor model. Complementary indices indicate that its multifactorial structure is the most adequate. Considering that 90% of the participants are women, the results show the CQ is a valid instrument for measuring co-parenting in Brazilian women.